Islamic Sufism and Spiritual Education: Moral Transcendence And Its Impact on Society - Remiswal Remiswal; Junizar Suratman; Meirison Meirison (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
The spiritual dimension of religions, in general, is the general feature of those religions and their ultimate goal that they seek to find, jumping over those ethnic, identitarian, or creedal dams that they created, either the whims of writers or the interpreters of sacred texts or the intended desires of those who framed religious laws, and all of that moved away, in one way or another, from the spirit of those religions and God's purpose in this is that of servitude to Him, the bridging of brotherhood, and the reconstruction of the land without oppression, killing or displacement through economic, religious, political, and social services for religion to be a deterrent to civilization and progress, not to be a symbolic basis for oppression, extremism, and the abolition of the other. We researched literature study and approached the phenomena that exist in the source in descriptive analysis and found spiritual values can refine man and give him limitless energies for the sake of goodness, truth, and love. That striving in competition, conflict of interests, clash of desires, and clash of civilizations. would make life a cruel and terrible struggle were it not for the care of God who revealed the Qur'an, guidance, and mercy for people. Accordingly, spiritual security and peace is the real riser of civilizations, and no civilization will arise unless it combines civilization and spirit. Therefore, this nation needs a serious application of Sufism and needs a spiritual education that aspires to charity and calls for virtue and abandonment of vice.